Identification of The Phases of The Spread of Covid-19 in Maluku Province with Richards Curve - Nanang Ondi; Yopi Andry Lesnussa; Francis Yunito Rumlawang (LPPM Institut Teknologi Sepuluh Nopember, 2021)
Richards Curve is an extension of the Logistics Curve which was first discovered in 1959 and is a type of sigmoid curve where in the sigmoid curve there are 3 growth phases, namely the logarithmic phase, the linear phase and the aging phase. This research aims to identify and determine the phase of the spread of COVID-19 in Maluku province with the Richards curve. From the calculation results obtained that the initial phase of the spread occurred on March 23 - July 5 2020, the peak phase of the spread occurred on July 6 - October 22 2020, the final phase of the peak of the spread occurred on October 23, 2020 - April 14, 2021 and began to enter the final phase of the spread on April 15, 2021.